Metastatic Renal Cell Carcinoma Mimicking Trigeminal Schwannoma in a Patient Presenting with Trigeminal Neuralgia - Wang, Arthur (J Neurol Surg Rep, 2015)
We present an unusual case of a metastatic renal cell carcinoma (RCC) mimicking trigeminal schwannoma. The patient, with no prior history of RCC, presented with clinical symptoms and imaging consistent with trigeminal neuralgia secondary to trigeminal schwannoma. Magnetic resonance imaging of the brain showed a large bilobed cystic/solid mass primarily in the cerebellopontine angle cistern, with extension into the left middle cranial fossa, Meckel cave, and left cavernous sinus. Following surgical excision, histopathology revealed the tumor to be an RCC infiltrating into the trigeminal nerve fascicles. Further imaging and investigation revealed widespread metastasis to the vertebral bodies and long bones. Metastatic RCC to the trigeminal nerve is rare. Despite the development of more effective treatment modalities, the prognosis of metastatic RCC remains poor. To our knowledge, this is the first reported case of RCC metastasizing to the trigeminal nerve fascicles.